Excellent Service Dimension from the Early Childhood Education Institute - Wahyuni, Sri; Supriyono, Supriyono (Journal of Nonformal Education, 2019)
The purpose of this study is to identify and explain the dimensions that determine the best services from PAUD institutions. This research is qualitative research with a multisite study design in three 1PAUD institutions in Malang City. Data were collected through in-depth interview techniques, participant observation, and documentation studies. The data analysis technique used is the inductive analysis techniques. This study yields findings that excellent services from PAUD institutions are determined by 5 dimensions, namely (1) dimensions of distinctiveness, which are reflected in curriculum content that highlights religious values, character, and life skills; (2) the dimension of trust, which is built from educators who are friendly, patient, painstaking, and caring for children; (3) comfort dimensions, which are formed from operating sites far from noise, clean school environment conditions, complete infrastructure facilities, adequate game equipment, and the availability of security personnel (security guards); (4) dimensions of hope, which are built from the form of full-day services through integrated service patterns; and (5) the affordability dimension, which is built from providing easy financing facilities, for example through cross-subsidies, installments, assistance or social assistance, and the absence of other fees beyond the planned costs.Â